Preparation of Mg/Nano‐HA Composites by Spark Plasma Sintering Method and Evaluation of Different Milling Time Effects on Their Microhardness, Corrosion Resistance, and Biocompatibility1 . Issue 1 (19th September 2016) - Guo, Pushan; Cui, Zeqin; Yang, Lijing; Cheng, Linxin; Wang, Wenxian; Xu, Bingshe
Abstract : Herein, Mg/nano‐HA composites (10 wt% nano‐HA) are prepared by spark plasma sintering (SPS) technique. Indeed, hydroxyapatite (HA) is used as reinforcement material in order to maintain biocompatibility and bioactivity. The influence of high energy ball milling time are considered by different methods. The study finds that an appropriate time (5 h) during high energy ball milling process effectively can eliminate the prior particle boundary (PPB). Furthermore, the Mg/nano‐HA composites milled for 5 h has appropriate microhardness, stable corrosion resistant, and excellent biocompatibility, which can act as a potential candidate for orthopedic implants. Abstract : Mg/nano‐HA composites are prepared by Spark Plasma Sintering (SPS) method. This study finds that an appropriate time (5 h) during high energy ball milling process effectively can eliminate the prior particle boundary (PPB). And also it is a good choice for the preparation of Mg‐based composites with desirable microhardness, stable corrosion resistant, and excellent biocompatibility.